2021
DOI: 10.3389/fonc.2021.772482
|View full text |Cite
|
Sign up to set email alerts
|

A Postsurgical Prognostic Nomogram for Locally Advanced Rectosigmoid Cancer to Assist in Patient Selection for Adjuvant Chemotherapy

Abstract: BackgroundThe perioperative treatment model for locally advanced rectosigmoid junction cancer (LARSC) has not been finalized; whether this model should refer to the treatment model for rectal cancer remains controversial.MethodsWe screened 10,188 patients with stage II/III rectosigmoid junction adenocarcinoma who underwent surgery between 2004 and 2016 from the National Cancer Institute Surveillance, Epidemiology, and End Results database. Among them, 4,960 did not receive adjuvant chemotherapy, while 5,228 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Another study of patients with locally advanced rectosigmoid colon cancer identi ed factors such as age, tumor grade, tumor size, T stage, and positive lymph nodes. These were independent prognostic factors in patients without adjuvant chemotherapy [19]. Similar conclusions were observed in a study of the prognostic risk of RC.…”
Section: Discussionsupporting
confidence: 86%
“…Another study of patients with locally advanced rectosigmoid colon cancer identi ed factors such as age, tumor grade, tumor size, T stage, and positive lymph nodes. These were independent prognostic factors in patients without adjuvant chemotherapy [19]. Similar conclusions were observed in a study of the prognostic risk of RC.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Du et al developed a risk strati cation method using a nomogram for the identi cation of uterine carcinoma patients who may bene t from PORT based on a large population database [11]. In addition, Zhang et al built a risk evaluator using a nomogram that successfully screened candidates for POCT among patients with locally advanced rectosigmoid cancer [12]. Therefore, we aimed to develop a novel risk strati cation method based on a nomogram to effectively select pIII-N2 NSCLC candidates for PORT after primary resection.…”
Section: Introductionmentioning
confidence: 99%
“…By scoring each single predictor, total scores can be obtained in different stages of the disease, enabling the prognosis prediction in a more intuitive manner [ 11 ]. A model for the perioperative treatment of locally advanced rectosigmoid colon has been previously established by Chao Zhang and colleagues [ 12 ]. This study showed that the current perioperative neoadjuvant therapy for rectal cancer is different from that of RSJC, and proved that lymph node positivity is an important factor in the selection of treatment for patients with locally advanced RSJC [ 12 ].…”
Section: Introductionmentioning
confidence: 99%